In vitro and in vivo evaluation of didymin cyclodextrin inclusion complexes: characterization and chemosensitization activity - Qing Yao; Meng-Ting Lin; Qing-Hua Lan; Zhi-Wei Huang; Ya-Wen Zheng; Xue Jiang; Yin-Di Zhu; Longfa Kou; He-Lin Xu; Ying-Zheng Zhao (Taylor & Francis Group, 2020)
Didymin is a dietary flavonoid that first found in citrus fruits, and possesses antioxidant properties. Our preliminary experiments first discovered that didymin was able to sensitize the resistant cancer cells against chemotherapeutics and combat multidrug resistance. However, its poor aqueous solubility and resultant low bioavailability limit its potentials as an adjuvant phytochemical drug for chemotherapy. Thus, this study prepared the inclusion complex of didymin with β-cyclodextrin and 2-hydroxypropyl-β-cyclodextrin to improve its bioavailability and then evaluate their chemosensitization effects. The didymin inclusion complexes formulation was prepared and their host-guest structure was characterized by FT-IR, PXRD, DSC, and SEM techniques. In vitro/in vivo results demonstrated that didymin inclusion complex enhanced its water solubility and orally bioavailability. Furthermore, didymin inclusion complex exerted considerable chemosensitivity potency, and improve the anti-tumor effects of chemotherapeutics in vivo. Therefore, didymin inclusion complex could provide a safe, effective, economical, and adjuvant drug for future treatment of chemoresistant cancers.